The usefulness of hysteroscopy in postmenopausal women with suspected ultrasonographic images of endometrium - Suzin, Jacek; Kowalczyk-Amico, Katarzyna; Gottwald, Leszek; Wierzbowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Summary Postmenopausal women with suspected ultrasonographic images like exceeded endometrial thickness, heterogenic endometrial echo or intrauterine fluid presence need histopathological verification. These images may concern not only endometrial pathology like malignant and non-malignant proliferations or intrauterine adhesions but also uterine muscle abnormalities like submucous myomas. Despite the abnormal ultrasonographic image, histopathological abnormalities in the endometrial “blind biopsy” frequently cannot be found. Objectives: Evaluation of hysteroscopy in the verification of abnormal ultrasonographic images of endometrium in postmenopausal women. Materials and methods: 56 postmenopausal women aged 49–77 without hormonal replacement therapy hospitalized in the 1st Department of Gynecology and Gynecological Oncology of the Medical University of Łódź in 1998–2002 because of abnormal ultrasonographic images of endometrium were investigated. In each case diagnostic hysteroscopy with visualization of the uterine cavity was performed and then histopathological biopsy by way of curettage was performed. Hysteroscopic images were analyzed and compared with the histopathological results. Results: 2 women had suspected hysteroscopic images in oncological terms. In both cases endometrial adenocarcinoma was histopathologically confirmed. One patient with exceeded endometrial thickness in vaginal ultrasound during hysteroscopy showed intrauterine adhesion which in histopathological examination appeared to be adenocarcinoma. In all 7 patients with hysteroscopic images suggesting non-malignant endometrial proliferation, endometrial hyperplasia was found. 17 times hysteroscopic visualisation of endometrial polyps enabled their complete detruncation. In 12 cases intrauterine adhesions were found and disrupted. 15 patients showed submucous myomas during hysteroscopic investigation. Any patient with the absence of hysteroscopically found uterine abnormalities had a poor histopathological result. Conclusions: Hysteroscopic investigation is very useful in the verification of abnormal ultrasonographic images of endometrium in postmenopausal women particularly in the visualisation of endometrial polyps and intrauterine adhesions. Hysteroscopic investigation in postmenopausal women with abnormal ultrasonographic images of endometrium reduce the risk of false negative histopathological result.